Geological map of the Dominion of Canada [1901] - Robert Bell (Producer)
Geological map of the Prairies and western part of the Dominion of Canada as of 1901. Legend on the right side is colour-coded to denote geological periods and epochs, along with acidic and basic rocks. Cities, towns, mountains, and bodies of water are named. Railroads can be seen throughout. Scale is 1:3,168,000. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ . There is a note on the lower left corner of the map going into detail of why certain areas are labelled a certain way.